CONVENTIONAL TEACHING VERSUS COMPUTER-ASSISTED LEARNING IN EXPERIMENTAL PHARMACOLOGY AMONG 2ND-YEAR MBBS STUDENTS: A QUESTIONNAIRE-BASED STUDY - NIVEDITA SAHA; DOLLY ROY; DEVARSI CHOUDHURY; PRANAB DAS (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The primary objective was to evaluate the effectiveness of CAL in improving students’ understanding of pharmacological concepts. The secondary objective was to assess students’ acceptance and preference for CAL compared to traditional teaching methods. Methods: A prospective cross-sectional study was conducted with 128 second-year MBBS students at Silchar Medical College & Hospital, Assam. Participants were divided into two groups: one group was taught using traditional methods, while the other utilized CAL. Data were collected through post-session quizzes and a feedback questionnaire. Statistical analysis included Chi-square tests to determine the significance of differences between the two groups. Results: The CAL group demonstrated significantly higher understanding and application of pharmacological concepts, with students reporting greater satisfaction and increased interest in the subject. Key findings include a significant improvement in understanding (χ² = 11.25, p = 0.023) and the ability to relate drugs to basic mechanisms (χ² = 10.54, p = 0.032). However, concerns about the resource requirements of CAL were noted (χ² = 9.98, p = 0.041). Conclusion: CAL significantly enhances the learning experience in experimental pharmacology, improving student comprehension, application of knowledge, and engagement. Despite its advantages, the implementation of CAL requires careful consideration of resource constraints. The study suggests that a hybrid approach, combining CAL with traditional methods, may offer the most effective strategy for teaching pharmacology.